2013
DOI: 10.1093/humrep/det016
|View full text |Cite
|
Sign up to set email alerts
|

A protein isolated from human oviductal tissue in vitro secretion, identified as human lactoferrin, interacts with spermatozoa and oocytes and modulates gamete interaction

Abstract: This study was supported by grants from FONCYT (PICT 01095, S.A.G., M.J.M) and SECyT UNR (PIDBIO238, S.A.G). The authors have no conflict of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 50 publications
5
56
1
2
Order By: Relevance
“…It was detected in tubal fluid and appeared to be estrogen regulated in human oviduct epithelial cells (Zumoffen et al 2013). Results of our study indicated that lactoferrin presents different binding patterns to sperm related to the capacitation status and the acrosome reaction, suggesting that the protein could participate in sperm-oocyte interaction ( Fig.…”
Section: Lactoferrinmentioning
confidence: 62%
See 3 more Smart Citations
“…It was detected in tubal fluid and appeared to be estrogen regulated in human oviduct epithelial cells (Zumoffen et al 2013). Results of our study indicated that lactoferrin presents different binding patterns to sperm related to the capacitation status and the acrosome reaction, suggesting that the protein could participate in sperm-oocyte interaction ( Fig.…”
Section: Lactoferrinmentioning
confidence: 62%
“…Results of our study indicated that lactoferrin presents different binding patterns to sperm related to the capacitation status and the acrosome reaction, suggesting that the protein could participate in sperm-oocyte interaction ( Fig. 3; Zumoffen et al 2013). In addition, lactoferrin was able to modulate some sperm functions related to capacitation (C Zumoffen and S Ghersevich unpublished observations).…”
Section: Lactoferrinmentioning
confidence: 80%
See 2 more Smart Citations
“…Lactoferrin, an oestrogen-regulated glycoprotein, was first identified in human OF. Depending on the sperm capacitation status, this protein exhibited different binding patterns, suggesting its involvement in gamete interaction (Zumoffen et al 2013). Oviductin, or oviduct-specific glycoprotein (OVGP1), is an oestrus-associated protein that has been demonstrated to be highly conserved in all species studied (Aviles et al 2010).…”
Section: Oviductal Fluidmentioning
confidence: 99%